Paper containing aerogel powder and aramid polymer fibrils

A paper composite of aerogel powder and aramid polymer fibrils addresses the challenges of thermal management and safety in battery systems by providing effective thermal insulation and flame protection while maintaining mechanical strength and high aerogel powder retention.

JP7667174B2Active Publication Date: 2025-04-22DUPONT SAFETY & CONSTRUCTION INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022555675
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-17
Filing Date
2021-03-15
Publication Date
2025-04-22
Estimated Expiration
2041-03-15

AI Technical Summary

Technical Problem

Existing flame shielding and thermal insulation materials for battery cells, modules, and packs face challenges such as high degradation rates, dust issues, and reduced yield, which affect their performance and safety in preventing thermal runaway and fires.

Method used

A paper composite made from 60-95 weight percent aerogel powder and 5-40 weight percent aramid polymer fibrils, with a thickness of 50-4000 micrometers, is developed for use as flame shielding or thermal insulation in battery applications. This combination traps aerogel powder particles within the aramid fibril network, enhancing retention and performance.

Benefits of technology

The paper composite provides improved thermal insulation with lower thermal conductivity and enhanced flame protection, retaining a high percentage of aerogel powder and maintaining mechanical strength, thus effectively addressing the challenges of thermal management and safety in battery systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667174000004
    Figure 0007667174000004
  • Figure 0007667174000005
    Figure 0007667174000005
  • Figure 0007667174000006
    Figure 0007667174000006
Patent Text Reader

Abstract

1. A paper suitable for use in a battery or battery pack as a flame breaker or thermal insulation material, the paper comprising 60 to 95 weight percent aerogel powder and 5 to 40 weight percent aramid polymer fibrils, the paper having a thickness of 50 to 4000 micrometers.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] TECHNICAL FIELD The present invention relates to a paper suitable for use in a battery cell, battery module, or battery pack as a fire shield or thermal insulation material; and to a battery cell, battery module, or battery pack including the paper. [Background technology]

[0002] 2. Description of the Prior Art: The growing use of lithium-ion and other batteries in electric vehicles has been accompanied by a significant increase in battery failures, including overheating and fires. Flame breakers and flame retardant insulation are needed for applications such as isolating battery cells to help prevent overheating and hot spots in one cell from resulting in a thermal runaway condition that could result in a fire or explosion in the entire battery pack.

[0003] Furthermore, some of the materials proposed for such insulators have properties that are undesirable to battery manufacturers. Some insulating materials have a high tendency to shed particles, either during manufacture or use, which is undesirable in that they cause dust and other problems in processes such as those requiring high speed automated adhesive tape application onto the surface of the insulation. Particle shedding also affects the bond between the surface of the insulation and the adhesive tape, causing movement and / or misalignment of the insulation due to vibrations (such as road vibrations) experienced by most electric vehicles during normal operation. Furthermore, material lost during manufacture is a yield loss that is undesirable.

[0004] What is needed is a fire protection construction that can provide improved thermal insulation and have acceptable shedding performance both during manufacture and during use, and that can be used in applications requiring fire protection or thermal insulation, such as various locations in a battery cell, battery module, or battery pack. Summary of the Invention [Means for solving the problem]

[0005] The present invention relates to a paper suitable for use in a battery or battery pack as a flame breaker or thermal insulation material, the paper comprising 60 to 95 weight percent aerogel powder and 5 to 40 weight percent aramid polymer fibrils, and having a thickness of 50 to 4000 micrometers. [Brief description of the drawings]

[0006] [Figure 1] 1A and 1B are SEM photographs at 500x and 1000x magnification, respectively, of the surface of paper made from a combination of aerogel powder and aramid polymer fibrils. [Diagram 2] 1A and 1B are SEM photographs at 500x and 1000x magnification, respectively, of the surface of paper made from a combination of aerogel powder and aramid polymer fibrils. [Diagram 3] 1A and 1B are cross-sectional views at 500× and 1000× magnification, respectively, of calendered or pressed paper made from a combination of aerogel powder and aramid polymer fibrils. [Figure 4] 1A and 1B are cross-sectional views at 500× and 1000× magnification, respectively, of calendered or pressed paper made from a combination of aerogel powder and aramid polymer fibrils. [Diagram 5] 1A and 1B are SEM photographs at 500x and 1000x magnification, respectively, of the surface of paper made from a combination of aerogel powder, aramid polymer fibrils, and mica. [Figure 6] 1A and 1B are SEM photographs at 500x and 1000x magnification, respectively, of the surface of paper made from a combination of aerogel powder, aramid polymer fibrils, and mica. [Figure 7] 1 is a plot of the thermal conductivity of several papers made from a combination of aerogel powder and aramid polymer fibrils, showing the effect of different amounts of total aerogel powder as well as aramid polymer fibrils on the thermal conductivity of the paper. [Figure 8] 1 is a digital photograph taken at 1000x magnification of aramid polymer fibrils. [Figure 9] This is a digital photograph taken at 500x magnification of a commercial aramid pulp. [Figure 10] 1 is a graphical representation comparing the distribution of pores in PPD-T / PVP filaments versus PPD-T filaments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The present invention relates to a paper suitable for use in a battery cell, battery module, or battery pack as a fire shield or thermal insulator, and a battery cell, battery module, or battery pack comprising the paper. The paper comprises 60-95 weight percent aerogel powder and 5-40 weight percent aramid polymer fibrils, the paper having a thickness of 50-4000 micrometers. This high percentage of aerogel powder in the sheet is made possible by the use of aramid polymer fibrils, which are believed to trap or confine the particles either by entanglement or by forming a mesh structure that does not allow the aerogel powder to flow out of the structure during papermaking.

[0008] The paper comprises 60-95 weight percent aerogel powder and 5-40 weight percent aramid polymer fibrils based on the total weight of the aerogel powder and aramid polymer fibrils in the paper. In some embodiments, the paper comprises 65-95 weight percent aerogel powder and 5-35 weight percent aramid polymer fibrils based on the total weight of the aerogel powder and aramid polymer fibrils in the paper. In some preferred embodiments, the paper comprises 75-95 weight percent aerogel powder and 5-25 weight percent aramid polymer fibrils based on the total weight of the aerogel powder and aramid polymer fibrils in the paper, and in some most preferred embodiments, the paper comprises 80-95 weight percent aerogel powder and 5-20 weight percent aramid polymer fibrils based on the total weight of the aerogel powder and aramid polymer fibrils in the paper.

[0009] Figures 1 and 2 are SEM photographs at 500x and 1000x magnification, respectively, of the surface of paper made from a combination of aerogel powder and aramid polymer fibrils, while Figures 3 and 4 are cross-sectional views at 500x and 1000x magnification, respectively, of calendered or pressed paper made from a combination of aerogel powder and aramid polymer fibrils.

[0010] The paper has a thickness of 100-4000 micrometers (0.1-4 millimeters). The minimum gap between cells (either pouch or prismatic cells) is approximately 0.1 mm, allowing current battery design standards and battery cell and module designers to miniaturize battery pack designs as much as possible due to the limited space inside electric vehicles. Therefore, a gap of more than 4 mm between two cells is generally undesirable. In some embodiments, the paper has a thickness of 300-3000 micrometers (0.3-3 millimeters). In some embodiments, the paper can have a basis weight of 50-500 grams per square meter. In some embodiments, the paper has a basis weight of 100-300 grams per square meter.

[0011] Aerogel refers to a porous, extremely lightweight synthetic material derived from a gel, where the liquid component of the gel has been replaced with a gas. The result is a solid with extremely low density and low thermal conductivity. Aerogels can be made from a variety of compounds, but silica aerogel is the preferred and most common type of aerogel.

[0012] As used herein, the terms "aerogel", "aerogel powder", and "aerogel particles" are all used interchangeably and refer to the preferred aerogels which are highly porous, hydrophobic, high surface area, preferably amorphous silica particles or granules having a particle size range of 10 nanometers to 50 micrometers (0.00001 to 0.05 millimeters), preferably 0.05 to 20 micrometers. Generally, they are chemically similar to common fumed silica products, but have higher porosity (>95%), lower density (0.03 to 0.1 g / cm). 3), small average pore diameter (20 nm), lower thermal conductivity (0.017–0.022 W / mK), higher surface area (600–800 m 2 Aerogels have larger aggregate sizes, higher surface areas and larger pore volumes, such as 0.15 to 1.5 mm (0.15 to 1.5 g), and are typically produced by a sol-gel manufacturing process. Pioneering patents describing aerogels include U.S. Pat. Nos. 2,093,454, 2,188,007, and 2,249,767 to Kistler, with more recent disclosures available such as U.S. Pat. Nos. 8,518,335 and 8,961,919 to Joung et al.

[0013] The term "aramid polymer fibrils" as used herein refers to hairy fibrous material having a diameter of 10 to 2000 nanometers, preferably 10 to 1200 nanometers, made from aramid polymers or polymer blends containing at least two polymers in which a majority (greater than 50 weight percent) of aramid polymer is present. FIG. 8 is a representative digital photograph of aramid polymer fibrils. The aramid polymer fibrils further have a preferred length of 0.2 to 3 millimeters. The "length" of fibrous materials referred to herein, such as aramid polymer fibrils and pulp, is meant to be the measured "length-weighted average" length. In some preferred embodiments, the aramid polymer fibrils are refined aramid polymer fibrils made from floc by subjecting the floc to a refining process that shears the floc into smaller aramid polymer fibrils. In some preferred embodiments, the aramid polymer fibrils have a length of 0.4 to 3 millimeters (mm), preferably 0.8 to 3 mm.

[0014] It is believed that the diameter of the aramid polymer fibrils influences the distribution and size of the pores in the paper structure when it is formed, providing a structure specifically designed to trap or entrap the aerogel powder. Aramid polymer fibrils with a diameter of more than 2000 nanometers will result in undesirably high pore sizes in the paper, which will ultimately result in large pores in the paper when it is formed, allowing the nano- and micro-sized aerogel powder to easily flow out during the papermaking process. Also, aramid polymer fibrils with a diameter of less than 10 nanometers or a length of less than about 0.2 millimeters will not contribute to the mechanical strength of the paper due to the lower entanglement of the aramid polymer fibrils, and therefore it is desirable for the majority of the aramid polymer fibrils to have a length of 0.2 millimeters or more.

[0015] Additionally, the aramid polymer fibrils have an aspect ratio that may range from about 150 to 300,000. Aspect ratio is also known as length divided by diameter, and the phrases "aspect ratio", "average length-to-diameter ratio" and "length-to-diameter" are used interchangeably herein. In some embodiments, the average length-to-diameter ratio of the aramid polymer fibrils is greater than or equal to about 1000. In some embodiments, the aramid polymer fibrils have an average length-to-diameter ratio of less than or equal to about 3000. In some preferred embodiments, the average length-to-diameter ratio ranges from about 1000 to 3000. It is believed that the higher average length-to-diameter ratio of the aramid polymer fibrils contributes to better mechanical reinforcement of the paper.

[0016] Because a qualitative measurement of certain fiber materials, such as aramid polymer fibrils, can be difficult, such fiber materials can be compared by measuring the "freeness" of the fiber materials. The most common techniques for measuring freeness measure either the Canadian Standard Freeness (CSF) or the Shopper-Riegler Freeness (SRF).

[0017] The inventors consider Canadian Standard Freeness (CSF) to be the preferred technique for characterizing aramid polymer fibrils for use herein. Aramid polymer fibrils are preferably produced by refining aramid polymer fibers or flocs to produce fibrils. Such fibrils preferably have a CSF of 0-50 milliliters, and in some embodiments, a CSF of 0-20 milliliters. The CSF is one measure of the fineness of the aramid polymer fibrils or the degree to which they are fibrillated during refining, with very fine aramid polymer fibrils having very low CSF. Also, materials with a wide size distribution generally have high CSF values, so a low CSF value indicates uniformly sized fibrils.

[0018] Aramid polymer fibrils as defined herein are fibrous materials and are quite different from aramid polymer pulps of the prior art. Such aramid polymer pulps may be preferably produced by refining flocs or directly from the ingredients taught in U.S. Pat. Nos. 5,202,184, 5,523,034, and 5,532,034. However, such methods not only provide fibrous materials with a wider range of fiber sizes and lengths due to the difficulty of controlling such methods, but can also provide both "stalks" and fibrils extending from the stalks, the stalks being roughly columnar remnants of the original aramid polymer flocs and having diameters of about 10 to 50 microns. Furthermore, in the case of aramid polymer pulps, the length measurement is understood to be the characteristic length of the pulp's stalks, also referred to as the "pulp stalks."

[0019] Also, the average length to diameter ratio of the aramid polymer fibrils is much greater than the average length to diameter ratio of conventional aramid polymer pulps, such as those made by the processes of U.S. Pat. Nos. 5,084,136, 5,171,402, and 8,211,272, which are believed to have average length to diameter ratios generally less than 150, or the average length to diameter ratio of highly refined pulps, such as those disclosed in U.S. Patent Application Publication Nos. 2016 / 0362525 and 2017 / 0204258, which are believed to be less than the average length to diameter ratio of conventional pulps (e.g., generally less than 100).

[0020] Further, aramid polymer fibrils, when used in paper, are aramid polymer fibrils that are essentially free of stalk or do not contain stalk. As used herein, the term "aramid polymer fibrils that do not contain stalk" means that at least 95% by weight of the fiber material are aramid polymer fibrils having a desired diameter of 10 to 2000 nanometers as determined by optical measurement of a fibril sample using 500x or 1000x magnification. In some embodiments, it means that at least 98% by weight of the fiber material are aramid polymer fibrils having a desired diameter of 10 to 2000 nanometers as determined by optical measurement of a fibril sample using 500x or 1000x magnification. In some embodiments, it means that 100% by weight of the fiber material are aramid polymer fibrils having a desired diameter of 10 to 2000 nanometers as determined by optical measurement of a fibril sample using 500x or 1000x magnification.

[0021] One preferred method of producing stalk-free aramid polymer fibrils is to refine fibers or flocs made from a polymer blend containing at least two polymers with a majority (greater than 50 weight percent) of the aramid polymer being present. One preferred polymer blend is a polymer blend of 80-96 weight percent polyparaphenylene terephthalamide (PPD-T) and 4-20 weight percent polyvinylpyrrolidone (PVP). When aramid fibers or aramid flocs made from this PPD-T / PVP polymer blend are refined, the resulting fiber material is essentially all fibrils with essentially no larger stalks present in the material, as shown in the digital photograph of FIG. 8. It is believed that at least 4 weight percent of PVP must be present in the fiber or floc in order for the original fiber or floc to be refined into fibrils with essentially no stalk remaining. This is in comparison to conventional refined aramid pulp made from polyparaphenylene terephthalamide (PPD-T) homopolymer, shown in FIG. 9, which has visible stalks.

[0022] The porosity and crystallinity of filaments made from blends of 80-96 weight percent PPD-T and 4-20 weight percent PVP have been found to be dramatically different from filaments consisting of PPD-T alone. The term "fiber" is used interchangeably with the term "filament" herein. Fibers spun directly onto bobbins from a polymer solution without cutting are commonly referred to as continuous fibers or filaments, and multifilament yarns contain multiple continuous filaments.

[0023] FIG. 10 illustrates the difference in x-ray scattering for the two types of filaments. Curve 20 represents a filament of the PPD-T / PVP blend, and curve 30 represents a filament made with PPD-T alone. Curve 30 illustrates that the PPD-T filament has a significant peak centered at about 2 Angstroms (and a much smaller peak centered at 4 Angstroms), indicating very small pores in the fiber. Curve 20 illustrates that the pore size distribution for the PPD-T / PVP blend is much broader, with a peak centered at about 3 Angstroms and a very broad sloping peak centered at about 250 Angstroms, but extending over a region ranging from about 70 to 600 Angstroms. This is believed to indicate that the filament made from the PPD-T / PVP blend has a significantly greater number of pores that are much larger than the PPD-T filament.

[0024] Moreover, due to this difference in the crystallinity and pore structure of the fibers, it is believed that mechanically refining the filaments results in much finer and more uniformly distributed fibrils, as illustrated in Figure 8. In other words, the very high crystallinity and low porosity of the PPD-T fibers means that when mechanically refined, the refining shear action primarily abrades the surface of the filaments to produce the typical fibril-with-stalk structure (as shown in Figure 9), whereas the low crystallinity and high porosity of the PPD-T / PVP blend filaments would allow them to easily separate into individual refined fibrils under the same shear action, with numerous fibrils of smaller and relatively more uniform diameter, and more importantly, essentially absent any stalks (i.e., no stalks). The aramid polymer fibrils are believed to have a relatively uniform diameter with a total diameter size range of about 300 nanometers, as visually measured from SEM micrographs.

[0025] Aramid polymer fibrils are preferably produced from aramid floc having PPD-T as the majority polymeric material component by weight and at least one other polymeric material component, which components are preferably mutually immiscible such that at least two polymeric materials are present in the floc as well-mixed but separate solid phases. Such aramid floc, when refined, produces aramid polymer fibrils having domains of two different polymeric materials, one phase being a continuous or primary polymer phase or PPD-T polymer and the other phase being a discontinuous or secondary polymer phase, which in the preferred case is a PVP polymer.

[0026] The discontinuous or secondary polymer phase is believed to exist as small nanometer-sized crystalline domains of material that pass through the floc and act as break points in the floc structure during the refining process, facilitating faster and more complete refining of the floc to form fibrils. After refining, a portion of the discontinuous or secondary polymer from each break point is present on or at the surface of each fibril resulting from the refining process.

[0027] Aramid polymer fibrils also have a high surface area. The terms "surface area," "specific surface area," and "BET surface area" are used interchangeably herein. Aramid polymer fibrils have a surface area of ​​about 3 to 40 m. 2 In some embodiments, the specific surface area is 6 m 2 / g or more, and in some embodiments the specific surface area is 8 m 2 / g or more. One particularly preferred range of the specific surface area is 6 to 20 m 2 / g.

[0028] In comparison, conventional pulp refined from floc made from a single polymeric material or from a miscible blend of polymeric materials that does not have discrete secondary polymer domains would not have such a high surface area. Moreover, if the floc were refined sufficiently to have such a high measured surface area, the resulting pulp particles would have such low aspect ratios (resulting from a very low average length) that they would not provide sufficient reinforcement for paper.

[0029] The preferred aramid fibrils contain 80 to 96 weight percent poly(paraphenylene terephthalamide) (also known and used herein as polyparaphenylene terephthalamide or PPD-T). By PPD-T is meant the homopolymer resulting from the mole-for-mole polymerization of p-phenylenediamine and terephthaloyl chloride, and also the copolymer resulting from the incorporation of small amounts of other diamines and small amounts of other diacid chlorides along with p-phenylenediamine and terephthaloyl chloride. Typically, the other diamines and other diacid chlorides can be used in amounts up to about 10 mole percent of the p-phenylenediamine or terephthaloyl chloride, or perhaps slightly higher, provided only that the other diamines and diacid chlorides do not have reactive groups that will interfere with the polymerization reaction. PPD-T also refers to copolymers obtained from the incorporation of other aromatic diamines and other aromatic diacid chlorides, such as 2,6-naphthaloyl chloride or chloro- or dichloro-terephthaloyl chloride, provided only that the other aromatic diamines and aromatic diacid chlorides are present in amounts that allow the preparation of anisotropic spinning dopes. The preparation of PPD-T is described in U.S. Pat. Nos. 3,869,429, 4,308,374 and 4,698,414.

[0030] The preferred aramid fibrils also contain 4 to 20 weight percent poly(vinylpyrrolidone) (also known and used herein as polyvinylpyrrolidone or PVP). By PVP is meant a polymer resulting from the linear polymerization of monomer units of N-vinyl-2-pyrrolidone and containing small amounts of comonomers that may be present at concentrations below those that do not interfere with the interaction of the PVP with the PPD-T. PVPs with molecular weights ranging from a minimum of about 5000 to a maximum of about 1,000,000 can be used. Very high molecular weight PVPs produce high viscosity spin dopes. PVPs with molecular weights of about 10,000 to about 360,000 are preferred.

[0031] Aramid polymer fibrils are preferably made by solution spinning continuous filament yarns from a dope containing an aramid polymer, cutting the continuous filament yarns into flocs, and then mechanically refining the flocs into fibrils using one or more refiners. In a preferred method, the dope is a solution containing a combination of PPD-T and PVP polymers in sulfuric acid. Examples of representative processes for making continuous filament yarns can be found in U.S. Pat. Nos. 5,073,440 and 5,094,913 and U.S. Patent Application Publication No. 2006 / 0113700. The aramid flocs are then cut from the continuous filament yarns. Prior to refining, the aramid flocs generally have a length of about 2 millimeters to about 25.4 millimeters, and sometimes 2 to 10 millimeters or even 3 to 10 millimeters.

[0032] Aramid polymer fibrils are preferably produced from the floc by refining or fibrillating the preferred PPD-T / PVP floc using techniques to cut, pulp or grind the PPD-T / PVP floc using mechanical methods that are convenient for paper, such as dry and wet disk or cone refining, hydrapulping and beating. Preferably, refining is performed on a dispersion of the floc in water, and preferably the dispersion is refined by multiple passes through a refiner, i.e. the refined dispersion leaving the refiner is recycled through the same or a second refiner for a second pass through the refiner, etc. The starting dispersion generally has a solids content of about 1-4 percent by weight of the floc in water.

[0033] If the floc is a PPD-T / PVP floc, it may be completely fibrillated into stalk-free aramid polymer fibrils after just three passes through the refiner and is then suitable for making paper. The stalk-free aramid polymer fibrils have a very low Canadian Standard Freeness (CSF) compared to pulps made from fibers that tend to fibrillate to form mixtures containing large amounts of stalk combined with the fibrils. Suitable fibrils are obtained with three passes through the refiner, although further passes through the refiner are possible and as many as 20 or more passes are believed to be helpful in further dispersing and homogenizing the fibrils, provided that they are not detrimental to the final strength of the paper. Preferably, the fibrils are made by recirculating the dispersion through the refiner for 3 to 20 passes, with some embodiments using 3 to 10 passes through the refiner.

[0034] It is believed that, with sufficient care, stalk-free aramid polymer fibrils can be obtained from traditional PPD-T, acrylic, or cellulose pulps if subsequent processes after the refining step are used to separate or recover the fibrils from the stalk. If such fibrils meet the definition of "stalk-free" as described herein, they are believed to be suitable fibrils for use in paper.

[0035] If desired, the paper can further include mica in an amount of 10 weight percent or more based on the total weight of the aerogel powder, aramid polymer fibrils, and mica in the paper. It is believed that the addition of mica in the paper structure further enhances the fire barrier and dimensional stability of the paper. The planar or flake shape of mica provides anisotropic fire barrier (in the z-direction perpendicular to the plane of the flakes) and the thermal conductivity in the z-direction is 1 / 100 of the thermal conductivity in the xy-directions. Planar mica advantageously aligns with and within the planar structure of the paper, so that the z-direction properties of mica provide improved thermal insulation across the plane of the paper. At least 20 weight percent mica in the paper is desirable in some cases to provide superior dimensional stability and fire barrier.

[0036] 5 and 6 are SEM photographs at 500× and 1000× magnification, respectively, of the surface of paper made from a combination of aerogel powder, aramid polymer fibrils, and mica.

[0037] Mica includes muscovite or phlogopite mica, or blends thereof, and may be calcined or uncalcined. As used herein, "calcined mica" refers to mica obtained by heating natural mica to high temperatures (usually above 800°C, sometimes above 950°C). This treatment removes water and impurities and improves the temperature resistance of the mica. Calcined mica is usually used in the form of flake particles, with muscovite type mica being preferred. As used herein, "uncalcined mica" refers to mica in its essentially high purity natural form, preferably homogenized and refined to remove defects and impurities. Uncalcined mica can form a highly porous mica layer due to the larger size of the natural mica flakes. The preferred mica is calcined mica due to its improved dielectric properties and corona resistance over uncalcined mica.

[0038] The term aramid as used herein means an aromatic polyamide in which at least 85% of the amide (-CONH-) bonds are directly attached to two aromatic rings. Additives may be used with the aramid and may be dispersed throughout the polymer structure. It has been found that up to about 10 weight percent of other support materials can be blended with the aramid. It has also been found that copolymers having up to about 10 percent of other diamines to replace the diamines of the aramid, or up to about 10 percent of other diacid chlorides to replace the diacid chlorides of the aramid can be used. The aramid may preferably be a para-aramid or an aramid copolymer. An aramid polymer is considered to be para-aramid when the two rings or radicals are oriented para to each other along the molecular chain. Methods for producing para-aramid fibers are generally disclosed, for example, in U.S. Pat. Nos. 3,869,430, 3,869,429, and 3,767,756. One preferred para-aramid is poly(paraphenylene terephthalamide) and one preferred para-aramid copolymer is copoly(p-phenylene / 3,4' diphenyl ester terephthalamide). U.S. Patents 3,063,966, 3,227,793, 3,287,324, 3,414,645 and 5,667,743 describe other methods for producing aramid fibers.

[0039] Specifically, a desirable commercially suitable process for making the paper of the present invention involves the use of a papermaking machine by feeding an aqueous dispersion containing aerogel powder and aramid polymer fibrils and any optional materials in the desired amounts and ratios into the headbox of the papermaking machine, then uniformly wet-laying and dispersing these solids as a web onto a papermaking wire, and removing most of the liquid water. The wet web can then be dried on a dryer drum to form paper. In some embodiments, the paper can preferably be further calendered or pressed under pressure and heat in the nip of a hot roll calender or by other means to consolidate and densify the paper into a layer having the desired thickness and properties. If necessary, two or more lighter basis weight or thinner wet webs of the same composition can be produced separately and then calendered together to consolidate into a single layer.

[0040] Representative equipment and machinery that can be used to make paper include, for example, but are not limited to, continuous processing equipment such as a Fourdrinier or inclined wire machine, or batch processing equipment such as equipment that makes paper manually in a handsheet form that includes a forming screen. For a general process of forming aramid materials into paper, reference can be made to U.S. Patent No. 3,756,908 to Gross and U.S. Patent No. 5,026,456 to Hesler et al.

[0041] In some embodiments, the paper has a tensile strength of 0.5 to 100 megapascals (MPa). In some applications, it is desirable for the paper to have a tensile strength of at least 15 megapascals or more. For example, it is believed that the paper requires this level of tensile strength to withstand some battery manufacturing processes, which may include the automatic insertion of flame shields and insulation between cells. The tensile strength also contributes to flame shielding during use. Paper tensile strengths above 100 megapascals do not have adverse effects, but the parameter reaches a point where the value is reduced. Thus, in some preferred embodiments, the paper has a tensile strength of 15 to 50 megapascals. In some embodiments, the paper has a tensile strength of 15 to 100 megapascals.

[0042] In some embodiments, the paper has a thermal conductivity of 0.015 to 0.05 Watts per meter Kelvin (W / mK). To effectively prevent heat propagation, paper with a lower thermal conductivity that is stable over a wide range of operating temperatures, such as battery operating temperatures (-40°C to 80°C), and up to thermal hotspot temperatures (800°C to 1,000°C) is preferred. In some embodiments, the paper has a thermal conductivity of 0.015 to 0.04 W / mK.

[0043] In some embodiments, a 1 mm (+ / - 30%) thick paper comprising aerogel powder and aramid polymer fibrils exhibits a TPP flame performance of at least 10 seconds to the equivalent of a second degree burn as measured by the Thermal Performance Protection Test (TPP), and in some embodiments, the paper exhibits a TPP flame performance of at least 12 seconds to the equivalent of a second degree burn.

[0044] It is believed that there is a synergistic effect on the thermal and mechanical properties of the resulting paper from the combination of aerogel powder and aramid polymer fibrils. The paper of the present invention shows a definite increase in voltage resistance with increasing mica content, but also a definite decrease in mechanical strength and toughness (tensile strength and elongation). However, increasing the amount of aerogel powder leads to improved thermal insulation (lower thermal conductivity) as well as better flame protection (TPP). In some cases, the paper of the present invention containing a combination of aerogel powder and aramid polymer fibrils has nearly 1 / 3 the thermal conductivity (i.e., greater insulation properties) while providing nearly 75% greater thermal protection (TPP) when compared to paper made by simply mixing mica, aerogel, and fibrids together and making paper. These significant properties as well as the significant improvement in shedding problems indicate that these papers are suitable for use as battery thermal insulation and fire breakers (cell-to-cell, cell-to-module, module and pack interior, etc.).

[0045] Multi-cell battery structures, with battery cells arranged either in parallel or in series, are commonly known as battery blocks and battery packs. In these multi-cell battery structures, thermal energy from an abnormal thermal event, such as a defect or failure in one cell, can propagate to adjacent cells. If the thermal events are severe enough, they can propagate from cell to cell and cause a runaway thermal condition that can cascade to all cells in the battery block or pack, resulting in a fire or worse.

[0046] To protect adjacent battery cells from an overheated cell, a better flame barrier and flame retardant insulation has low thermal conductivity and high dimensional stability at higher temperatures. When a thermal event occurs, the overheated cell temperature can rise to 800°C and above. However, adjacent cells should be kept below 200°C. Therefore, the thermal insulation between adjacent cells is preferably sufficiently thermally stable up to at least 800°C.

[0047] Batteries including the paper described herein can be manufactured by using the paper as inter-cell insulation. "Inter-cell insulation" is intended to include materials inserted between individual battery cells in a multi-cell battery construction that provide thermal insulation, i.e., they thermally isolate each battery cell and also tend to slow the transfer of thermal energy should a battery cell have an abnormal thermal problem, such as thermal runaway, that could result in a thermal "hot spot" or explosion.

[0048] In one application, the paper is inserted between individual battery cells in a multi-cell battery structure to provide a fire barrier and thermal insulation between the individual battery cells. Exemplary battery types include, but are not limited to, multi-cell battery structures having battery cells arranged in either parallel or series, commonly known as battery blocks and battery packs. However, other batteries including the paper are possible, as the described paper is intended to thermally isolate each battery cell and retard the transfer of heat energy and / or flame from one cell to another cell or structure.

[0049] Test Method In the examples provided below, the following test methods were used:

[0050] Thickness: 5N / cm 2 The measurements were made according to TAPPI 411 using the weight of the material and recorded in mm.

[0051] Basis weight is measured in accordance with ASTM D 645 and ASTM D 645-M-96 and is in g / m 2 It was recorded.

[0052] Tensile strength was measured according to ASTM D 828-93 using a 2.54 cm wide specimen and a gauge length of 18 cm and was reported in N / cm or MPa.

[0053] Dielectric strength was measured according to ASTM D149-97A and reported in kV / cm.

[0054] Thermal conductivity was measured according to ASTM E1530 and reported in W / mK.

[0055] The Thermal Performance Protection Test (TPP) is a measure of the flammability performance of material fabrics and sheets, providing realistic conditions of exposure to a combination of radiant and convective heat. Samples are subjected to conditions typical of ignition, i.e. 84 kW / m 2 (2cal / cm 2 The material is exposed to a constant heat flux of 80kW / m2 (1000m2 / sec), a constant combination of 50% radiant and 50% convective heat. The test then measures the time it takes for the temperature and energy transferred to the back of the fabric to reach a level equivalent to a second degree burn if the material is worn, and the amount of thermal energy per surface area (TPP value). The TPP test method used is 80kW / m2. 2 This test method has been adopted by ISO as the standard for test methods involving heat flux exposure of 84 kW / m2 (ISO 17492). However, the US NFPA 1971 standard defines the ISO 17492 test as 2 and this higher heat flux was used herein. EXAMPLES

[0056] Example 1 Four different papers, designated 1-1 to 1-4, were made from aramid polymer fibrils and aerogel powder. The aramid polymer fibrils had a Canadian Standard Freeness of 0 ml and a Canadian Standard Freeness of 13.8 ml. 2The aramid polymer fibrils were composed of 87 weight percent PPD-T and 13 weight percent PVP and had an average length-to-diameter ratio of about 2000. The aerogel powder was type IC3100 Enova® aerogel obtained from Cabot Corp. of Boston, MA. Four well-mixed aqueous dispersions were prepared having different amounts of aramid polymer fibrils and aerogel powder but all had approximately the same solids content of 0.18% and had the compositions shown in Table 1.

[0057] Each of the four aqueous dispersions was then poured into a 21 x 21 cm handsheet mold with approximately 8 liters of water to create a furnish having approximately 0.05% total solids to form wet laid handsheets. Each handsheet was then removed, placed between two pieces of blotter paper, hand couched with a cotton swab, and dried in a handsheet dryer at 150°C for 10 minutes. The paper was then dried and showed a smooth, grain free surface. As shown in Figure 1, the aerogel powder particles were trapped within the nanofibril network around the particles. The properties of the resulting paper structure are listed in Table 1.

[0058] Comparative example A Comparative Paper A was made by first forming an aqueous dispersion of 8 grams of aerogel powder and 2 grams of MPD-I fibrids in water. The fibrids did not contain any aerogel polymer. The MPD-I fibrids were made as generally described in U.S. Pat. No. 3,756,908.

[0059] As used herein, the term fibrids refers to very small non-granular, fibrous or film-like particles with at least one of their three dimensions being an order of magnitude smaller than the largest dimension. These particles are prepared by precipitating a solution of a support material with a non-solvent under high shear. Aramid fibrids are non-granular film-like particles of aromatic polyamides having a melting or decomposition point above 320°C. The preferred aramid fibrids are meta-aramid fibrids, and especially preferred are fibrids made from meta-aramid poly(meta-phenylene isophthalamide) (MPD-I).

[0060] Fibrids generally have a maximum dimension length in the range of about 0.1 mm to about 1 mm with a length to width aspect ratio of about 5:1 to about 10:1. The thickness dimension is on the order of a fraction of a micron, e.g., about 0.1 micron to about 1.0 micron. Undried fibrids were used in the dispersion.

[0061] The aqueous dispersion was then used to form handsheets as in Example 1. The dried paper exhibited a rough, de-grained surface. The physical and thermal properties are shown in Tables 1 and 2.

[0062] TGA (thermogravimetric analysis) of the dried paper showed that a residual amount of aerogel particles weighing about 5.15 grams remained, which means that nearly 51.2% of the original aerogel powder was lost during the papermaking process. The data in Table 2 shows the synergistic effect on the thermal and mechanical properties of the paper resulting from the combination of mica and aerogel-containing fibrids. The paper shows a significant increase in dielectric strength with increasing mica content, but also a significant decrease in mechanical strength and toughness (tensile strength and elongation). However, increasing the amount of aerogel powder in the paper improved the thermal insulation (lower thermal conductivity) as well as better flame protection (TPP). Both the papers of Comparative Example A and Examples 2-3 were made using 20 weight percent aerogel powder. However, the paper of Examples 2-3 has nearly half the thermal conductivity (i.e., twice the insulating properties) and twice the thermal protection (TPP) of the paper of Comparative Example A. These outstanding properties, as well as the significant improvement in shedding problems, indicate that these papers are suitable for use as battery thermal insulation and fire protection (cell-to-cell, cell-to-module, module and pack interiors, etc.).

[0063] Comparative example B Comparative Paper B was made from an aqueous dispersion containing only fibrids. However, these fibrids were modified fibrids made from a polymer dispersion containing aerogel powder. In other words, the actual fibrids contained a blend of polymer and aerogel powder.

[0064] Specifically, a polymer dispersion was prepared by blending 65 parts by weight of the solvent dimethylacetamide, 15 parts by weight of poly(metaphenylene isophthalamide) (MPD-I) polymer, 5 parts by weight of calcium chloride (as a solubility enhancer), and 15 parts by weight of aerogel powder (Type IC 3100 Enova® aerogel obtained from Cabot Corp., Boston, MA) in a kettle with stirring until a homogenous mixture was obtained. The mixture was then slowly poured into a vigorously stirring Waring blender, which simultaneously coagulated the polymer from the solvent into membrane-like fibrids, where the MPD-I polymer and aerogel powder were present in a 1:4 ratio. The resulting modified fibrids were collected on a Buchner funnel as wet-laid paper and washed thoroughly with deionized water. Aqueous dispersions and handsheets were prepared using these modified fibrids using the procedure of Example 1. The compositions and test results are shown in Tables 1 and 2.

[0065] To analyze the different amounts of silicate and therefore the amount of aerogel immobilized in all samples, TGA thermogravimetric analysis (TGA) was performed on all of 1-1 to 1-4 and comparative A and B papers using a high resolution TA Instruments Q500 TGA (40-700C) in air. The results are shown in Tables 1 and 2. As expected, the paper samples made by simply mixing the fibrids and aerogel powder together showed the highest reduction of aerogel in the final structure, retaining just 64% of the aerogel powder added. The paper samples made by encapsulating the aerogel within the fibrids performed better, retaining 71% of the aerogel powder. Surprisingly, however, the paper samples made by mixing the aramid polymer fibrils with the aerogel powder increased the retention of the aerogel powder to over 90%, ranging from 92 to 95% for the four paper samples. This fully explained that the aerogel powder particles were trapped in the network of aramid polymer fibrils.

[0066] The thermal conductivity was then measured for these paper samples by the thin film method using a non-stationary planar heat source (TPS1500) using 2.45 kg pressure on a 2 inch diameter laminate sample. The practical effect of the retained aerogel particles on the thermal conductivity of the paper samples is shown graphically in FIG. 7. The paper samples made by mixing the aramid polymer fibrils with the aerogel powder samples had the lowest thermal conductivity, and when the thermal conductivity of all samples made at 80 weight percent added aerogel level were compared, Examples 1-3 were found to have thermal conductivities 29% and 22% lower than Comparative Examples A and B, respectively.

[0067] [Table 1]

[0068] [Table 2]

[0069] Example 2 Paper was made from aerogel powder, aramid polymer fibrils, and mica. The paper had lower thermal conductivity and higher flame resistance when compared to paper without mica or an equivalent amount of aerogel powder.

[0070] Two separate aqueous dispersions were prepared using the procedure of Example 1. However, a significant amount of calcined mica flake was added to the two dispersions, replacing 10 and 20 percent by weight, respectively, of the aerogel powder in the two dispersions, as shown in Table 3. The mica was a muscovite type available from Electrical Samica Flake Co., Rutland, Vermont. Handsheets were then prepared using the procedure of Example 1 and tested for burn performance. All dried papers exhibited a smooth, grain-free surface. The compositions and test results are shown in Table 3.

[0071] [Table 3] The present disclosure includes the following embodiments. <Embodiment 1> 1. A paper suitable for use in a battery or battery pack as a flame breaker or thermal insulation material, comprising: 60 to 95 weight percent of an aerogel powder; and 5 to 40 weight percent aramid polymer fibrils; Paper having a thickness of 50 to 4000 micrometers. <Embodiment 2> 2. The paper of embodiment 1, further comprising mica in an amount of 10 weight percent or greater, based on the total weight of the aerogel powder, aramid polymer fibrils, and mica in the paper. <Embodiment 3> 3. The paper of claim 1 or 2, wherein the aramid polymer fibrils comprise poly(paraphenylene terephthalamide). <Embodiment 4> 4. The paper of embodiment 3, wherein the aramid polymer fibrils comprise a blend of polymers, the blend of polymers comprising 80 to 96 weight percent poly(paraphenylene terephthalamide) and 4 to 20 weight percent poly(vinylpyrrolidone). <Embodiment 5> 5. The paper according to any one of the preceding claims, having a thickness of 500 to 3000 micrometers. <Embodiment 6> 6. The paper according to any one of embodiments 1 to 5, having a tensile strength of 0.5 to 100 MPa. <Embodiment 7> 7. The paper according to any one of the preceding embodiments, having a thermal conductivity of 0.015 to 0.05 W / mK. <Embodiment 8> A battery cell, a battery module, or a battery pack comprising the paper according to any one of embodiments 1 to 7.

Claims

1. 1. A paper suitable for use in a battery or battery pack as a flame breaker or thermal insulation material, comprising: 60 to 95 weight percent aerogel powder; and 5 to 40 weight percent aramid polymer fibrils; The paper has a thickness of 50 to 4000 micrometers.

2. 10. The paper of claim 1, further comprising mica in an amount of 10 weight percent or greater, based on the total weight of the aerogel powder, aramid polymer fibrils, and mica in the paper.

3. A battery cell, a battery module, or a battery pack comprising the paper according to claim 1 or 2.

Citation Information

Patent Citations

  • Thermal insulation fireproof composite material and preparation method thereof

    CN103306157A

  • Aramid complex sheet, preparation thereof and electric and electronic equipment and appliances having the same

    JP1998130496A

  • Flame resistant barrier paper composition

    JP2003520310A

  • Composite sheets and cargo containers containing them

    JP2017519656A

  • High tensile strength paper suitable for use in electrochemical cells

    US20200056332A1